ฮิวแมนแปบปิโลมาไวรัส ชนิดที่ 16 ในรอยโรคไลเคนแพลนัส อีพิทีเลียล ดิสแพลเซีย และมะเร็งสควอมัส เซลล์ คาร์ซิโนมาในช่องปากของผู้ป่วยไทย - กล้าวจี เกตุแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Human Papillomavirus (HPV) is an epitheliotropic virus which known to cause benign and malignant tumors of the mucosal epithelium including oral mucosa. HPV-associated oral lesions are mostly low-risk HPV, but high-risk HPV are also associated with malignant lesions. Oral lichen planus (OLP), epithelial dysplasia, oral squamous cell carcinoma (OSCC) and normal mucosa in paraffin sections were evaluated for HPV-16 with HPV-16L1 antibody by immunohistochemistry. HPV-16 was detected in 26.7% (16/60) of OLP, 73.3% (22/30) of epithelial dysplasia, 23.3% (7/30) of OSCC, and 15% (3/20) of normal mucosa, and the detection rate of HPV-16 in epithelial dysplasia was higher than that in OSCC, OLP and normal mucosa being statistically significant. The mean age of the group with normal mucosa was significantly lower than that in other groups. Long-term follow up on patients with presence of HPV in normal mucosa is recommended. This study confirms findings of HPV-16 prevalence in epithelial dysplasia. We concluded that HPV-16 may be involved in the pathogenesis of epithelial dysplasia. HPV-16 in association with other factors may induce pathological changes in the progression of potentially malignant lesions to malignancy.